2011
DOI: 10.1007/s11199-011-9969-5
|View full text |Cite
|
Sign up to set email alerts
|

System Justification, Right-Wing Conservatism, and Internalized Homophobia: Gay and Lesbian Attitudes toward Same-Sex Parenting in Italy

Abstract: Adopting a system justification perspective (Jost and Banaji 1994), we investigated the manner and extent to which gay men and lesbians might internalize a sense of inferiority when it comes to parenthood. In an Italian sample of gay and lesbian individuals, we found that gay men who scored high (versus low) on system justification and right-wing conservatism regarded same sex parents as less competent; these effects were mediated by internalized homophobia. Lesbian women, however, perceived lesbian parents as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 54 publications
(58 reference statements)
8
79
0
8
Order By: Relevance
“…Previously conducted studies have showed that negative positions exceed positive ones (Araújo et al, 2007;Cerqueira-Santos & Santana, 2015;Pacilli, Taurino, Jost, & van der Toorn, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Previously conducted studies have showed that negative positions exceed positive ones (Araújo et al, 2007;Cerqueira-Santos & Santana, 2015;Pacilli, Taurino, Jost, & van der Toorn, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…O que pode ser percebido em pesquisas realizadas previamente e demonstraram que os posicionamentos negativos, sobressaiam aos positivos (Araújo et al, 2007;Cerqueira-Santos & Santana, 2015;Pacilli, Taurino, Jost, & van der Toorn, 2011).…”
Section: Discussionunclassified
“…The research in the field has been typically conducted at the micro level and has attempted to understand the variables that explain the tolerance/intolerance of individuals towards homosexuality and the rights of homosexuals (Larsen et al, 1980;Lewis, 2003;Brewer and Wilcox, 2005;Andersen and Fetner, 2008;Adamczyk and Pitt, 2009;Schwartz, 2010;Baunach, 2012;Becker, 2012;Pacilli et al, 2011;Van den Akker et al, 2012). Other literature has contributed to the understanding of issues such as health, education or employment in the LGBT community (Robinson and Ferfolja, 2001;Lambert et al, 2006) or to the analysis of LGBT associations (Calvo and Trujillo, 2011).…”
Section: Understanding the Recognition Of Homo-parental Adoptive Righmentioning
confidence: 99%